The Fuzzy Cognitive Mapping of Stakeholders Related to the Measured Fishing Policy (In Southeast Sulawesi) - Robin; Taswin Munie, Muhammad; Hamka, Eddy; Mansyur, La Ode (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2025)
The issuance of the Measured Fishing Policy (PIT) has sparked controversy among fishing communities, particularly due to its mechanism, which is seen as granting greater opportunities for the fishing industry to exploit marine resources. In contrast, small-scale and traditional fishers are perceived to be at a disadvantage in the long run. This study aims to examine the perceptions of fisheries stakeholders regarding the implementation of PIT, with research conducted in Fisheries Management Area (WPP) 714, especially in Southeast Sulawesi. A mixed-methods approach was applied, combining primary data from Focus Group Discussions (FGD), questionnaires, and in-depth interviews, alongside secondary data sourced from scientific articles, research reports, online media, and other references. The analysis using fuzzy cognitive mapping indicates that the PIT policy is negatively associated with fishermen’s income, fish stock sustainability, conservation efforts, and community involvement. Furthermore, the study reveals stakeholder perspectives on seven key characteristics of measurable fishing policies, with the quota system emerging as the most prominent concern among fisheries practitioners and observers. In conclusion, the fuzzy cognitive mapping results highlight that PIT is largely perceived as having adverse impacts on small-scale fisheries.